Measurement of glycine in healthy and tumorous brain by triple‐refocusing MRS at 3 T in vivo. (26th May 2017) - Tiwari, Vivek; An, Zhongxu; Ganji, Sandeep K.; Baxter, Jeannie; Patel, Toral R.; Pan, Edward; Mickey, Bruce E.; Maher, Elizabeth A.; Pinho, Marco C.; Choi, Changho
Abstract : Glycine (Gly) has been implicated in several neurological disorders, including malignant brain tumors. The precise measurement of Gly is challenging largely as a result of the spectral overlap with myo‐inositol (mI). We report a new triple‐refocusing sequence for the reliable co‐detection of Gly and mI at 3 T and for the evaluation of Gly in healthy and tumorous brain. The sequence parameters were optimized with density‐matrix simulations and phantom validation. With a total TE of 134 ms, the sequence gave complete suppression of the mI signal between 3.5 and 3.6 ppm and, consequently, well‐defined Gly (3.55 ppm) and mI (3.64 ppm) peaks. In vivo 1 H magnetic resonance spectroscopy (MRS) data were acquired from the gray matter (GM)‐dominant medial occipital and white matter (WM)‐dominant left parietal regions in six healthy subjects, and analyzed with LCModel using in‐house‐calculated basis spectra. Tissue segmentation was performed to obtain the GM and WM contents within the MRS voxels. Metabolites were quantified with reference to GM‐rich medial occipital total creatine at 8 mM. The Gly and mI concentrations were estimated to be 0.63 ± 0.05 and 8.6 ± 0.6 mM for the medial occipital and 0.34 ± 0.05 and 5.3 ± 0.8 mM for the left parietal regions, respectively. From linear regression of the metabolite estimates versus fractional GM content, the concentration ratios between pure GM and pure WM were estimated to be 2.6 and 2.1 for Gly and mI, respectively. Clinical application of the optimized sequence was performed in four subjects with brain tumor. The Gly levels in tumors were higher than those of healthy brain. Gly elevation was more extensive in a post‐contrast enhancing region than in a non‐enhancing region. The data indicate that the optimized triple‐refocusing sequence may provide reliable co‐detection of Gly and mI, and alterations of Gly in brain tumors can be precisely evaluated. Abstract : We report evaluation of concentration difference of glycine (Gly) between gray and white matter in healthy brain and elevation of Gly in brain tumors, using a new triple‐refocusing sequence that enables reliable co‐detection of Gly and myo‐inositol at 3T. Gly was estimated to be 2.5‐fold higher in pure gray matter than in white matter. Gly elevation was extensive in aggressive tumors. Detection of marked elevation of Gly in a brainstem lesion helped make a radiographical decision on tumor aggressiveness.